قضايا نقدية وأدبية في كتابات الشيخ محمد الغزالي Literary and Critical Issues in the Writings of Sheikh Muhammad al-Ghazali - بطاهر (Benaissa Bettahar), بن عيسى (At-Tajdid - Intellectual Refereed Journal, 2011)
مستخلص البحث يعدّ الشيخ محمد الغزالي (1335/1917- 1416/1996) - رحمه الله - أحد كبار علماء الأمة الإسلامية في العصر الحديث، فقد كان من أبرز الدعاة إلى الإسلام بمنهجه الوسطي وخطابه المعتدل. وقد عاش صراعًا متصلاً ضد الأيديولوجيات الغريبة والأفكار الضارة، ووظّف كلّ طاقاته ومواهبه للدفاع عن الحقّ، وبعث روح الإيجابية والفاعلية في الأمّة الإسلامية، واستخدم قدراته البيانية والخطابية في توصيل الخطاب الدعوي إلى القراء والمخاطَبين بأسلوب أدبي جميل يجمع بين أصالة الفكرة وجمال التعبير الأدبي الرشيق. وفي كتابات الغزالي المتنوّعة كثيرٌ من القضايا الأدبية والنقدية التي عالجها من خلال ربطها بالقضايا المركزية للتجديد والتغيير في الحياة الفكرية والثقافية للمسلمين في القرن العشرين. وقد لفتت انتباهنا خمس قضايا: قضية الأدب الإسلامي، وقضية الأدب وعلاقته بالخطاب الديني، وقضية الأسلوب في الخطاب الدعوي، وقضية الشعر الحرّ، ومصير اللغة العربية. وقد جاءت هذه الدراسة للبحث في هذه القضايا المهمّة من أجل كشفها وتقويمها وبيان موقف الشيخ منها، كما أنّها شملت في جانبٍ منها قراءة نقدية استطلاعية في ديوانه "الحياة الأولى". الكلمات الأساسية: الإسلام، الفكر الإسلامي، الخطاب الديني، الدعوة إلى الإسلام، التجديد والتغيير، الأدب والنقد الأدبي، الأدب والخطاب الدعوي، اللغة العربية، التغريب الفكري والثقافي. Abstract Sheikh Muhammad al-Ghazali (1335/1917-1416/1996), may Allah bless his soul, is regarded as one of the great contemporary Islamic scholars of modern times. He was one of the most prominent advocates of Islam through his balanced approach and moderate discourse. He lived a life of continuous struggle against alien ideologies and pernicious ideas and cultures, using his full energies and talents to defend the truth and promote the spirit of constructive attitude and efficacy among the Muslim ummah. He used his strong rhetorical ability and eloquent style to convey the Islamic missionary discourse to the public, thus combining the originality of ideas and beauty of literary expression to reach out to his audience. Al-Ghazali’s diversified writings abound with many literary and critical issues which he tackled in relation to the central issues of renewal and change in Muslim intellectual and cultural life throughout the twentieth century. Of those literary and critical issues five have caught our attention, namely: Islamic literature, literature and its relationship with the religious discourse, the style in the Islamic missionary discourse, the new Arab poetry not abiding by the rules of classical meter prosody, and the future of the Arabic language. This study looks into these important issues and examine them critically so as to highlight al-Ghazali’s position regarding them. The study also includes an exploratory review of his dīwÉn titled al-×ayÉt al-ÕlÉ. Key terms: Islam, Islamic thought, religious discourse, call to Islam, renewal and change, literature and literary criticism, literature and Islamic missionary discourse, Arabic language, intellectual and cultural westernization. Abstrak Sheikh Muhammad al-Ghazali (1335/1917-1416/1996), dianggap sebagai salah satu ulama besar Islam kontemporari zaman moden. Dia adalah salah satu pendakwah Islam yang sangat menonjol melalui pendekatan yang seimbang dan wacana sederhana. Dia hidup dalam perjuangan terus-menerus melawan ideologi asing, idea-idea dan budaya yang merosakkan dengan menggunakan tenaga penuh dan bakat untuk membela kebenaran dan meningkatkan semangat sikap konstruktif dan kecekapan antara umat Muslim. Dia menggunakan kemampuan retoris yang kuat dan gaya yang fasih untuk menyampaikan wacana dakwah Islam kepada masyarakat, sehingga menggabungkan orisinalitas ide dan keindahan ekspresi sastera untuk menjangkau pendengarnya. Kepelbagaian tulisan Al-Ghazali penuh dengan masalah sastera yang kritis sehubungan dengan isu sentral pembaharuan dan perubahan dalam kehidupan intelektual muslim dan budaya sepanjang abad kedua puluh. Dari isu-isu kritis sastera ada lima hal yang menangkap perhatian kita, iaitu: sastera Islam, sastera dan hubungannya dengan wacana agama, gaya dalam wacana dakwah Islam, puisi Arab baru tidak mematuhi peraturan prosodi meter klasik, dan masa depan Bahasa Arab. Kajian ini melihat ke dalam isu-isu penting dan memeriksa mereka kritis sehingga untuk menyerlahkan kedudukan al-Ghazali. Kajian ini juga merangkumi kajian eksplorasi dīwÉn berjudul al-×ayÉt al-ÕlÉ. Istilah kunci: Islam, pemikiran Islam, wacana keagamaan, seruan kepada Islam, pembaharuan dan perubahan, sastera dan kritikan sastera, sastera dan wacana dakwah Islam, Bahasa Arab, intelektual dan westernisasi budaya.